2014
DOI: 10.5152/akd.2014.4824
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate recovery may predict the presence of coronary artery disease

Abstract: Objective: We investigated whether post-exercise first minute abnormal heart rate recovery (HRR1) helps to predict the presence and severity of CAD, because of some confounding data. Methods: A cross-sectional, retrospective study was performed. Two hundred individuals were included. Gensini scores and the number of coronary artery involvements were used to evaluate the severity of CAD. Student's t-test, Mann-Whitney U test and chi-square test were used for the analysis continuous and categorical data. Spearma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
2
22
1
1
Order By: Relevance
“…Together, these findings indicate that parasympathetic system activity is suppressed during exercise and during the first minute of recovery and then steadily increases until 4 min post-exercise and remains stable until 10 min post-recovery (23, 26). Alterations in HRR indices have been previously investigated in heart failure (27)albeit not fully recognized, in the development of vascular complications in diabetes mellitus (28), ischemic heart disease (18, 22), obstructive sleep apnea (29), pulmonary arterial hypertension (30), systemic lupus erythematosus (31) and its impairment is an independent prognostic indicator for cardiovascular and all-cause mortality. Doğru et al (15) demonstrated decreased HRR values in patients with ED; however, HRR indices have not been separately evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these findings indicate that parasympathetic system activity is suppressed during exercise and during the first minute of recovery and then steadily increases until 4 min post-exercise and remains stable until 10 min post-recovery (23, 26). Alterations in HRR indices have been previously investigated in heart failure (27)albeit not fully recognized, in the development of vascular complications in diabetes mellitus (28), ischemic heart disease (18, 22), obstructive sleep apnea (29), pulmonary arterial hypertension (30), systemic lupus erythematosus (31) and its impairment is an independent prognostic indicator for cardiovascular and all-cause mortality. Doğru et al (15) demonstrated decreased HRR values in patients with ED; however, HRR indices have not been separately evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Stress exercise test qualification was determined if the heart rate reached 85% of the target rate. Patients walked for a 2-min cool-down period at a 1.5-mph speed and 2.5% grade (18). The decrease in heart rate from the peak rate (HRR indices) was measured during the cool-down period at the 1 st , 2 nd , 3 rd , and 5 th minutes after cessation of the stress test and are denoted as HRR 1 , HRR 2 , HRR 3 , and HRR 5 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…KHTİ efor testi sırasında ulaşılan en yüksek kalp hızından istirahat 1. dakika kalp hızı çıkarılarak tespit edildi. KON tanısı daha önce tanımlandığı şekilde KHTİ'nin ≤ 21 bulunması ile konuldu (10) .…”
Section: Hastalar Ve Yöntemunclassified
“…We read with great interest the article, entitled “Heart rate recovery may predict the presence of coronary artery disease” by Akyüz et al (1) published in Anatolian J Cardiol 2014; 14: 351-6.…”
mentioning
confidence: 99%